'Candidatus Megaira' are diverse symbionts of algae and ciliates with the potential for defensive symbiosis. Issue 3 (10th March 2023) - Davison, Helen Rebecca; Hurst, Gregory D. D.; Siozios, Stefanos
Abstract : Symbiotic microbes from the genus 'Candidatus Megaira' ( Rickettsiales ) are known to be common associates of algae and ciliates. However, genomic resources for these bacteria are scarce, limiting our understanding of their diversity and biology. We therefore utilize Sequence Read Archive and metagenomic assemblies to explore the diversity of this genus. We successfully extract four draft ' Ca . Megaira' genomes including one complete scaffold for a ' Ca . Megaira ' and identify an additional 14 draft genomes from uncategorized environmental metagenome-assembled genomes. We use this information to resolve the phylogeny for the hyper-diverse ' Ca . Megaira', with hosts broadly spanning ciliates, and micro- and macro-algae, and find that the current single genus designation ' Ca . Megaira' significantly underestimates their diversity. We also evaluate the metabolic potential and diversity of ''Ca . Megaira' from this new genomic data and find no clear evidence of nutritional symbiosis. In contrast, we hypothesize a potential for defensive symbiosis in 'Ca . Megaira ' . Intriguingly, one symbiont genome revealed a proliferation of ORFs with ankyrin, tetratricopeptide and leucine-rich repeats such as those observed in the genus Wolbachia where they are considered important for host–symbiont protein–protein interactions. Onward research should investigate the phenotypic interactions between 'Ca . Megaira ' and their various potential hosts, including the economically important Nemacystus decipiens, and target acquisition of genomic information to reflect the diversity of this massively variable group.